Genetic Analysis of Highly Inbred Chicken Using RAPD-PCR and Immunocompetence - Chatterjee, R.N.; Sharma, R.P.; Reddy, B.L.N.; Niranjan, M.; Shivaprasad; Mishra, S.K. (International Journal of Poultry Science, 2007)
The data of G-5 generation of inbred and non-inbred populations of Dahlem Red were utilized in the present study. These populations were originally developed by a regular system of full sib and half sib mating for 5 successive generations. A random mated non-inbred population was also maintained. Consequently, 3 sub populations have been developed from the same base population, namely, a full sib mated group (FS), a half sib mated group (HS) and a non-inbred group (NB). The inbreeding coefficient in the G-5 generation in the FS group and HS groups was 67.2% and 44.9%, respectively. These three sub populations were subjected to PCR-RAPD analysis to observe the genetic distance and similarity between different subpopulations. A total of 41 random primers (decamers) were screened for RAPD analysis, out of which 21 primers amplified the genomic DNA, generated 128 to 4544 bp bands. The Mean Average Percentage Difference (MAPD) varied between 13.22 and 22.20. The MAPD was highest between FS and NB and lowest between HS and FS. The intra-population genetic similarity was highest in FS (0.7139) followed by HS (0.7095) and NB (0.7054) which indicated that FS subpopulation is most uniform. The FS and NB had maximum genetic distance (by both band sharing and band frequency) and FS and HS had lowest genetic distance. The immune response to SRBC was highest in NB group followed by FS and HS groups.